Relationship between secondary nutrients of apple leaves and control of the Codling Moth (Cydia pomonella L., Lepidoptera: Tortricidae) by low doses of sugars - Tiffrent, Abdelkader; Lombarkia, Nadia; Lebbal, Salim (ENTOMOLOGIA HELLENICA, 2025)
The codling moth (Cydia pomonella L., 1758) regularly causes considerable damage in orchards, leading to extensive use of chemical insecticides. Many studies have focused on the relationship between nutrients and plant pests and diseases, and several sound reviews link the two issues. The aim of this study is to investigate the effect of sugar spraying at infra-doses on the nutrients present in apple leaves, in comparison with a control and a reference insecticide (deltamethrin), to understand the mechanisms leading to apple tree resistance to the codling moth. The results obtained highlighted that glucose, fructose and insecticide treatments significantly increased the concentrations of calcium, magnesium, boron, chlorides and iron compared to the untreated control. Additionally, the glucose treatment increased the concentration of manganese whereas it decreased the concentration of copper. In conclusion, infra-dose sugar spraying modified the nutritional status of the leaves, and this modification probably influences plant resistance to the codling moth.